STEAM Approach in Childhood Teaching and Learning: A Comparative Study in Indonesia and Nigeria - Palupi Sri Wijayanti; Jamiu Sulaimon (SEAMEO CECCEP, 2025)
Abstract—Science, Technology, Engineering, the Arts and Mathematics (STEAM) integrations in countries Education contribute to the development and innovation of countries Education. This study investigated Steam approach in childhood teaching and learning: a comparative study in Indonesia and Nigeria. The study adopted a descriptive survey design, which was guided by two research questions and one hypothesis. The population of the study was early childhood and primary education teachers in Indonesia and Nigeria. Multistage sampling techniques were used to select 164 respondents. A researcher self-constructed instrument titled “Steam Approach in Childhood Teaching and Learning Questionnaire’ (SACTLQ), with a reliability index of 0.79. The data obtained was analysed using descriptive statistics and inferential statistics of T-test at 0.05 level of significance. The study brought to light the available documents and resources for STEAM teaching in Nigeria and Indonesia which include curriculum documents, teaching materials on instructional needs, lesson plans, and documentation and a comprehensive portfolio of teaching resources. The study's findings also revealed that the STEAM program's integration level in schools in Indonesia and Nigeria is high. Finally, there was no statistically significant difference in the level of STEAM program integration between primary schools in Indonesia and Nigeria. It was therefore recommended that the Nigeria and Indonesia governments keep formulating and implementing policies that support STEAM integration in schools alongside cross-encouraging cross-country collaboration between Nigeria and Indonesia in STEAM integration.